Design, Fabrication, and Testing of Active Skin Antenna with 3D Printing Array Framework - Jinzhu Zhou; Haitao Li; Le Kang; Baofu Tang; Jin Huang; Zhiheng Cai (International Journal of Antennas and Propagation)
An active skin antenna with structural load-bearing and electromagnetic functions is usually installed in the structural surface of mobile vehicles such as aircrafts, warships, and high-speed train. This paper presents the design, fabrication, and testing of a novel active skin antenna which consists of an encapsulation shell, antenna skin, and RF and beam control circuits. The antenna skin which consists of the facesheet, honeycomb, array framework, and microstrip antenna elements was designed by using Bayesian optimization, in order to improve the design efficiency. An active skin antenna prototype with 32 microstrip antenna elements was fabricated by using a hybrid manufacturing method. In this method, 3D printing technology was applied to fabricate the array framework, and the different layers were bonded to form the final antenna skin by using traditional composite process. Some experimental testing was conducted, and the testing results validate the feasibility the proposed antenna skin structure. The proposed design and fabrication technique is suitable for the development of conformal load-bearing antenna or smart skin antenna installed in the structural surface of aircraft, warships, and armored vehicles.